Variation of Sugar and Fermentation Duration Influence the Chemical Profile of Kombucha Cascara - Pineapple - Shabrina Puteri Pratama; Ajeng Brahmanti; Hadi Munarko (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
This research investigates the influence of various carbon sources (cane sugar, honey, palm sugar) and fermentation durations (7, 10, 13 days) on the chemical profile of a functional drink, kombucha, made from pineapple-fermented cascara. A Completely Randomized Design (CRD) with two factors was conducted to analyze the interaction between two variables. Analyzed parameters include antioxidant activity, total phenolic content (TPC), total titratable acidity (TTA), total sugar, and total dissolved solids. The results reveal that palm sugar combined with a 10-day fermentation period yields the highest antioxidant activity (326.78 mg AAE/L) and TPC (848.76 mg GAE/L). SCOBY microbial metabolism demonstrated significant efficiency, Total titratable acidity (TTA) increased during fermentation, particularly in the sucrose treatment, from 1.92% to 3.33%. In contrast, total sugar decreased from 27.29% to 17.15%. Total soluble solids (TSS) fluctuated during fermentation, with the highest value observed in the palm sugar treatment fermented for 10 days at 13.67°Brix. This research highlights an innovative way to valorise coffee cherry waste into a health-promoting drink by enhancing its flavour through natural fruit fermentation. Contribution to Sustainable Development Goals (SDGs):SDG 3: Good Health and Well-BeingSDG 12: Responsible Consumption and Production